Study of the Civil Forfeiture System According to the United Nations Convention against Corruption - دهش, قائد هادي (Journal of Legal Sciences, 2019)
Civil Forfeiture is a controversial legal process that allows law enforcement authorities to seize assets when there is a suspicion that assets are the proceeds of crime, regardless of the accused’s conviction for crime. This process viewed on the one hand as a strong weapon for targeting criminal assets and means to commit further criminal activity, and on the other hand as a violation of the rights of individuals. Justifications have been introduced to support both sides. This Article examines those justifications, and supports the civil forfeiture system to be applied in Iraq. The Article proposes the core elements that need to be considered in adopting civil forfeiture legislation in Iraq.